Clinical Effect of Augmentin as Intracanal Medicament Compared with no any Medication on Endodontic Flare-Up in Cases of Symptomatic Apical Periodontitis- A Pilot Study (Medical Forum Monthly, 2023)
Objective: To assess the clinical effect of Augmentin as intracanal medicament on endodontic flare-up in comparison with no any intracanal medicament in cases of symptomatic apical periodontitis.Study Design: Comparative studyPlace and Duration of Study: This study was conducted at the Operative Dentistry Department, Dental OPD Liaquat University of Medical and Health Sciences, Jamshoro from June to October 2015.Materials and Methods: Total 50 patients requiring endodontic treatment were selected in this study. The patients were assigned into two groups by lottery method .The teeth of patients in group I were treated with Augmentin as ICM after cleaning and shaping and temporarily restored. In group II, the teeth were left with empty canals after complete cleaning and shaping and restored with temporary filling. Next appointment was given to patients after 24 hour and after one week to assess the level of inter-appointment pain.Results: The mean age of the patients was 30.42±7.754. The males and females were 42% and 58% respectively. The types of teeth were anterior and posterior 58% and 42% respectively. Teeth with pulpal status with irreversible pulpitis and pulp necrosis were 46% and 54% respectively. The mean value of preoperative pain level was 8.24±0.797, pain after 24 hours was 4.54±1.606 and after 7 days was 1.10±0.931. The association of study group and effectiveness on pain (control of pain) showed that in group 1, 70% effective and 25% not effective, as compared to group II 30% effective and 75% not effective with P value 0.001.Conclusion: It is concluded that “The patients in which Augmentin was used as intracanal medicaments showed a greater decrease in pain levels over the observation period when compared to the control group.”